2021
DOI: 10.1080/02634937.2021.1946483
|View full text |Cite
|
Sign up to set email alerts
|

‘End the dominance of the Uyghur ethnic group’: an analysis of Beijing’s population optimization strategy in southern Xinjiang

Abstract: Chinese academics and politicians argue that Xinjiang's 'terrorism' problem can only be solved by 'optimizing' its ethnic population structure. High ethnic minority population concentrations are considered a national security threat. 'Optimizing' such concentrations requires 'embedding' substantial Han populations, whose 'positive culture' can mitigate the Uyghur 'human problem'. Scenarios that do not overburden the region's ecological carrying capacity entail drastic reductions in ethnic minority natural popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There are reports of all types of torture inflicted upon detainees, including sexual torture, rape, and killing (Hill, Campanale, and Gunter 2021). And troubling accounts have emerged of Uyghur women being forced to have IUDs inserted into their bodies solely on account of their ethnicity, ever more clearly revealing a will to destroy an entire people (Zenz 2021).…”
Section: Knowing Genocidementioning
confidence: 99%
See 2 more Smart Citations
“…There are reports of all types of torture inflicted upon detainees, including sexual torture, rape, and killing (Hill, Campanale, and Gunter 2021). And troubling accounts have emerged of Uyghur women being forced to have IUDs inserted into their bodies solely on account of their ethnicity, ever more clearly revealing a will to destroy an entire people (Zenz 2021).…”
Section: Knowing Genocidementioning
confidence: 99%
“…First, reports emerged of the arbitrary mass detention of Uyghurs and other indigenous peoples of Turkic ethnic backgrounds in the region (Human Rights Watch 2017). Further details indicated that detainees were being held in concentration camps, forced to undergo political re-education that included patriotic indoctrination and the renunciation of their religious beliefs (Sulaiman 2017;Zenz 2019). In 2020, reports revealed that some detainees were being transferred out of these centers into forced labor programs that resembled modern-day slavery (Xu et al 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, China has a record of racism and xenophobia against both Black people (Sautman, 1994) and ethnic minorities in Xinjiang and Tibet, the latter two of which it considers domestic matters. These issues and sensitivity to BLM were further amplified by several factors: (a) The Covid-19 pandemic which augmented China's xenophobic and racist behaviour towards Black residents, raising concern from some of its own African allies (Pai, 2020; Williamson and Wang, 2020); (b) China's handling of the 2019 Hong Kong protests, the proposed extradition bill, and the granting of new sweeping powers to police forces to violently oppress protesters; (c) China's “re-education” of its ethnic minority people, the Uyghurs, in Xinjiang province, which is condemned as “genocide” and human rights abuse by many western countries (Smith Finley, 2021; Zenz, 2021).…”
Section: Introductionmentioning
confidence: 99%